2020
DOI: 10.5435/jaaos-d-17-00925
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Reduced With Intravenous Acetaminophen in Geriatric Hip Fracture Patients

Abstract: Introduction: Postoperative delirium is associated with opioid use in the elderly and is a common complication of geriatric hip fractures, with reported incidences from 16% to 70%. Intravenous (IV) acetaminophen is a safe and efficacious medication in elderly patients and has been shown to reduce use of opioids after hip fracture. At our institution, IV acetaminophen was implemented for the first 24 hours postoperatively as part of a multimodal pain control regimen for geriatric hip fracture patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…Studies [ 28 , 29 ] have shown that elderly patients with hip fractures ≥ 73 years of age are 1.83 times more likely to develop delirium after surgery than those aged < 73 years. Studies [ 30 , 31 ] have shown that age is attributable to preoperative malnutrition in elderly patients with medullary fractures, and it is one of the main risk factors of delirium in elderly patients, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Studies [ 28 , 29 ] have shown that elderly patients with hip fractures ≥ 73 years of age are 1.83 times more likely to develop delirium after surgery than those aged < 73 years. Studies [ 30 , 31 ] have shown that age is attributable to preoperative malnutrition in elderly patients with medullary fractures, and it is one of the main risk factors of delirium in elderly patients, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Studies [28,29] have shown that elderly patients with hip fractures ≥73 years of age are 1.83 times more likely to develop delirium after surgery than those aged <73 years. At the same time, studies [30,31] have shown that age is attributable to preoperative malnutrition in elderly patients with medullary fractures, and it is one of the main risk factors of delirium in elderly patients, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…13 Across surgical disciplines, studies have shown that multimodal analgesia, along with decreased opiate usage, may be associated with lower rates of POD. 14,15 Dexmedetomidine, an α-2 agonist with sedative and analgesic properties, has demonstrated an opioid-sparing effect in cardiac surgery patients 16 and has shown promise in reducing delirium in this patient population when used instead of propofol. 10 Acetaminophen may be particularly effective in reducing opioid requirements.…”
Section: Intravenous (Iv) Acetaminophen and Deliriummentioning
confidence: 99%
“…Overall, this study is consistent with a growing body of evidence indicating that nonopioid analgesia may contribute to decreased rates of POD across surgical specialties. 14,15 Further research is needed to confirm the specific utility of acetaminophen in reducing POD risk in cardiac surgery patients, as demonstrated in the DEXACET trial.…”
Section: Intravenous (Iv) Acetaminophen and Deliriummentioning
confidence: 99%